SOCIALIZING LOCAL WISDOM VALUES TO THE PEOPLE OF SOUTHEAST SULAWESI AS AN EFFORT TO PREVENT CORRUPTION - Abdul Jalil (Asia Pacific Fraud Journal, 2018)
An understanding of the values of local wisdom as one of the most important elements in preventing corrupt behavior should be encouraged and introduced to today’s generation, given that the current generation’s behavior has slowly abandoned the ancestral heritage that is full of meaning and content in life. All cultures certainly teach goodness to the people, especially the younger generation, but unfortunately they often fail to understand and even abandon the cultures, which in turn, their behaviors become uncontrollable. Their actions tend to drift from noble values. Some of the values of local wisdom studied in this paper include respecting the neighbors, avoiding and reconciling conflicts, appreciating others’ work and services, and gathering property in the right way